Epidemiology of Anterior Tibial Spine Fractures in Young Patients: A Retrospective Cohort Study of 122 Cases. Issue 2 (February 2019) - Axibal, Derek P.; Mitchell, Justin J.; Mayo, Meredith H.; Chahla, Jorge; Dean, Chase S.; Palmer, Claire E.; Campbell, Kristen; Vidal, Armando F.; Rhodes, Jason T.
Abstract : Background: Historically, bicycle accidents were described as the most common mechanism for pediatric anterior tibial spine fractures (ATSFs). There is a paucity of current literature examining the demographic factors associated with these injuries. The purpose of this cohort study was to characterize the epidemiology of ATSFs presenting to a single tertiary referral pediatric hospital. Methods: A consecutive cohort of 122 pediatric patients with ATSFs between 1996 and 2014 were reviewed. Radiographic variables, classification of fractures (Meyers and McKeever type), age, sex, height, weight, body mass index, and mechanism of injury were retrieved. Categories of mechanism of injury included organized sports (football, soccer, basketball, lacrosse, wrestling, and gymnastics), bicycling, outdoor sports (skiing, skateboarding, and sledding), fall, motor vehicle collision/pedestrian versus motor vehicle, and trampoline. Results: Organized sports-related injuries represented the most common cause of ATSFs (36%). Other common mechanisms of injury included bicycle accidents (25%), outdoor sports (18%), and falls (11%). There was a higher proportion of males (69%) compared with females (31%). Males (mean age, 11.6 y) were significantly older than females (mean age, 9.8 y) ( P =0.004). Younger patients (aged 11.5 y and below) were more likely to have displaced fractures (type III), whereas type I and type II were more common in patients above 11.5 years ( P =0.02). Patients with fracture type I were significantly taller than patients with fracture type III. No other variables were found to differ significantly according to fracture severity, including sex, weight, and body mass index. Conclusions: To our knowledge, our study represents both the largest (n=122) and most up-to-date epidemiological ATSF study in pediatric patients. A higher rate of ATSF occurs due to organized sports rather than bicycling or motor vehicle collision. This 18-year data collection represents a change in the paradigm, and is likely multifactorial, including increased participation in youth sports and early sport specialization. Level of Evidence: Level IV—retrospective, cohort study.